▼Aliskiren for hypertension in adults. Issue 10 (1st October 2008) - Unknown
Abstract : High blood pressure is a major risk factor for cardiovascular disease worldwide.1 Drug treatments include those that target the renin-angiotensin system, a key hormone cascade in the regulation of blood pressure. One of these is ▼aliskiren (Rasilez – Novartis), which belongs to a new class of drugs, direct renin inhibitors.2 Here we assess its place in managing adults with hypertension.